Analisis Manajemen Resiko Penerbangan Di Bandar Udara Sultan Muhammad Salahuddin Bima Berbasis ISO 31000 - Moch Irvan; Adipura Danang Maulana (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Sultan Muhammad Salahuddin Airport located in Bima Regency, West Nusa Tenggara is an airport located in Bima Regency, West Nusa Tenggara with IATA code: BMU. Which is managed by the Airport Operator Unit, namely UPT Directorate General of Hubud. Sultan Muammad Salahuddin Bima Airport as an aviation company in Indonesia, apparently has not implemented a risk management system that refers to ISO 31000. This study aims to determine the stages and processes of identifying, analyzing, and evaluating risks at Sultan Muhammad Salahuddin Bima Airport based on ISO 31000. This study used descriptive qualitative method. Data collection was done by observation, structured interviews and documentaries. Data analysis used in accordance with the risk management process using the ISO 31000 base, including risk identification, risk analysis, and risk evaluation. Measurement of the likelihood and impact of risk is performed using the FAA matrix. The results of this study are from the results of the author's risk identification of 12 hazards and 12 flight risks at Sultan Muhammad Salahuddin Bima Airport. Risk analysis that the author conducted to obtain risk events that could potentially occur in the Sultan Muhammad Salahuddin Bima Airport unit and the impact caused by these risks. The author's risk evaluation found that 9 risks in the red zone (high) and 2 risks in the yellow zone (medium) and 1 risk in the green zone (low) and requiring treatment or control.